Performance of two-stage rotary desiccant cooling system with different regeneration temperatures. (1st February 2015) - Ge, T.S.; Dai, Y.J.; Wang, R.Z.; Li, Y.
Abstract: Increasing attention is being given to energy-saving air conditioning technology in recent years. Using natural refrigerant and driven by low grade thermal energy, rotary desiccant cooling system has become a sound alternative solution to conventional vapor compression system. Although one-stage ventilation rotary desiccant cooling system is still the main stream, TSDC (two-stage rotary desiccant cooling) system recently emerges as the latest development, which can be driven by lower regeneration temperature (50–90 °C) compared with one-stage system. In this paper, performance of TSDC with different regeneration temperatures in two stages is analyzed. First integrated mathematical model of TSDC system is established by combing models of different components. Cooling power and COP th (thermal coefficient of performance) are utilized as performance indicators. Then system performance with respect to different combinations of two regeneration temperatures are simulated and discussed, while optimization investigation is also conducted to obtain maximum COP th with same cooling power. Under the simulation condition, results show that cooling power of the system increases with the increase of regeneration temperatures, however, COP th decreases. Also, when the first stage operates in higher regeneration temperature, TSDC system can obtain better performance reflecting in both cooling power and in COP th . Moreover, with the same cooling power provided, COP th of TSDC system obtains a minimum value when temperatures of the two stages approach. Highlights: Mathematical model of two-stage rotary desiccant cooling system is established and adopted. System performance is investigated under the condition of different regeneration temperature in the two stages. Optimization of thermal COP with different regeneration temperatures is analyzed. Higher regeneration temperature in the first stage is recommended. Minimum value of thermal COP exists with same cooling power.